Contribuindo para a compreensão da prática de copidesque: o gênero introdução de dissertação de mestrado - Aguiar, Andréa Pisan Soares (2011)
The processing of texts that will be public is an activity dating from the 3rd century b.C when the texts were produced by scribes in monasteries. Already in the 15th century, typographers, teachers and scholars began to carry out this work, obeying certain rules of standardization, hitherto non-existent. Currently, although the textual treatment stage is important, the presence of professionals to perform, namely, the proofreader and copyediting, is becoming less frequent in newspapers and publishers. It is common confusion in defining what is copyediting and what is proofreading. In copyediting, the professional performs textual complex interventions, which may change the structure of the text. In proofreading, the search for inaccuracies that have remained, as grammatical errors, as well as those related to the standardization of the text. In order to observe the changes suggested by copy writing and understand more comprehensively his acting, we selected as corpus texts belonging to the genre introduction of MSc dissertation, in the original and copyedited version. To achieve this goal, we were based on north-american genre studies, which Miller (2009a, 2009b, 2009c), Swales (1990, 2004), Bhatia (1993) and Bunton (1998, 2002); we take their methodological models to apply in this research, as well as, the studies of Bazerman (2006a, 2006b, 2007), for whom writing is "agency". Through this research it was possible to observe that the studies of genres, in particular those related to the rhetorical moves, can contribute greatly to the understanding and the improvement of copyediting